2013
DOI: 10.1007/s00384-013-1748-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of the pretreatment albumin/globulin ratio in predicting the long-term survival in colorectal cancer

Abstract: Low AGR was a strong independent predictor of long-term cancer-specific survival among colorectal cancer patients. Additionally, among the patients with normal albumin (>3.5 g/dl), patients with lower globulins but higher albumin and AGR levels had better survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
125
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 26 publications
6
125
1
Order By: Relevance
“…This has also been reported in various other cancers, e.g. breast [37], gastric [38], colorectal [39], endometrium [15], and ovarian [5,12]. Asher et al [12] assessed the median survival of EOC patients by pre-operative albumin level.…”
mentioning
confidence: 92%
“…This has also been reported in various other cancers, e.g. breast [37], gastric [38], colorectal [39], endometrium [15], and ovarian [5,12]. Asher et al [12] assessed the median survival of EOC patients by pre-operative albumin level.…”
mentioning
confidence: 92%
“…As systemic inflammation causes an increase in the levels of various proinflammatory cytokines, which subsequently promote tumor progression because of changes in the cancer microenvironment [19,20], a decreased AGR is thought to correlate with tumor progression. Recently, the AGR was reported to be a prognostic marker in patients with colorectal cancer, lung cancer, breast cancer, and nasopharyngeal carcinoma [16,[21][22][23]. However, there are no reports on the effect of the AGR on mortality in BUC.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, several previous studies have demonstrated the correlation between the preoperative AGR and long-term survival of cancers (9)(10)(11)(12)(13)(14), but GC has not been discussed. The purpose of this study was to find the cutoff value of AGR and to evaluate whether preoperative AGR has a prognostic value in patients with resectable GC.…”
mentioning
confidence: 99%